Co-creating a culturally relevant programme for enabling participation of children with brain injury in Uganda (CEBU) - Ekwan, Francis Uzu (Department of Health and Rehabilitation Sciences, 2025)
Background: The Culturally Relevant Programme Enabling Participation of Children with Brain Injury in Uganda was co-created to address the occupational needs of children with brain injury aged four months to 17 years, as well as the well-being of their caregivers. Aim and Purpose: The aim of this thesis was to co-create a culturally relevant programme for enabling participation of children with brain injury in Uganda and describe its co-creation process. The purpose was to improve children's activity functioning and survival following brain injury, and impact on caregivers' health. Methods: Three studies were implemented in two phases following participatory action research design. Phase one explored the participants' thoughts, feelings, and perceptions of the usual intervention in Kampala-Wakiso Brain Injury Home: Therapy Centre (KWB-HTC) Uganda. In phase two, a culturally relevant programme enabling participation of children with brain injury was co-created; its consequences and limitations described. Purposive selection of primary participants (eight brain injured children) and general participants (eleven health professionals and three caregivers) took place. Video data were collected from each primary participant in the usual intervention, action changes. Interview data were collected from general participants in group reflection and individual interview. Thematic analysis was used to analyse data collected. Findings: Thematic analysis of data collected identified three main themes: The first theme, “an intervention that does not satisfy basic needs,” linked to three sub-themes: “ignorance of child's condition,” “assessment that does not focus on functional issues,” and “unwitting goals.” The second theme, “bridging basic needs and enablement,” linked to three sub-themes: “assessing child enablement contexts,” “supporting caregivers to attain psychological health,” and “involving the child in daily life activities.” The third theme, “diversifying daily life participation,” linked to two sub-themes: “forming community connectedness,” and “moderating caregiver constraints.” Conclusion: In conclusion, every child with brain injury in Uganda deserves an intervention that satisfies basic needs, co-created as the Four-star Model for Enablement and Participation. To implement the Four-star Model, this thesis proposed Occupation Actualization (OA) philosophy which requires children with brain injury to be involved in daily life activities formed by occupation scale and occupation score. The Occupation Actualization philosophy assumes that there is a positive relationship between occupation scale, occupation score, and enablement within the guiding principles of the Four-star Model delivered through community connectedness at the African One Hospital. Further research is recommended to implement and evaluate the effectiveness of the Four-star Model in Uganda, and test the validity of the OA philosophy.